2020
DOI: 10.1177/1178223420911033
|View full text |Cite
|
Sign up to set email alerts
|

Informational Needs in Patients With Breast Cancer With Lymphedema: Is It Important?

Abstract: Introduction: Lymphedema is one of the complications of breast cancer treatment. It has no cure yet and can affect the quality of life. This study aimed to identify and investigate informational needs, preferred delivery methods, and time of receiving information about lymphedema for these patients. Methods: One hundred participants were recruited through Lymphedema Clinic in Motamed Cancer Institute in Tehran, Iran, through convenience sampling and were asked to complete a self-administered survey. Data colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Educational improvement of standard and professional guidance in monitoring swelling and implementing lymphedema drainage can alleviate patients’ anxiety and depression. 30 Web‐based multimedia interventions can make breast cancer patients receive more information than pamphlet education. 15 Meanwhile, the preference for private teaching sessions suggests the need for a remote one‐to‐one teaching strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational improvement of standard and professional guidance in monitoring swelling and implementing lymphedema drainage can alleviate patients’ anxiety and depression. 30 Web‐based multimedia interventions can make breast cancer patients receive more information than pamphlet education. 15 Meanwhile, the preference for private teaching sessions suggests the need for a remote one‐to‐one teaching strategy.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Meanwhile, the preference for private teaching sessions suggests the need for a remote one‐to‐one teaching strategy. 30 Nonetheless, timely diagnosis and treatment of lymphedema remain effective and direct measures. Our study showed that patients equally preferred treatment at hospital and self‐care at home.…”
Section: Discussionmentioning
confidence: 99%
“…It is the first common cancer accounting for 11.7% of all cancer worldwide [ 1 ]. It is the leading cause of cancer death in most countries [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly reported cancer for women is breast cancer [1]. A dynamic multi-step mechanism involving the spread of cancer cells from the breast to other parts of the body is metastatic breast cancer [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the world, 1.38 million women with breast cancer are diagnosed every year [3]. It is the leading cause of cancer mortality in most countries [1]. Breast Cancer is responsible for 2.09 million cases and 6,27,000 deaths worldwide, as per WHO [4].…”
Section: Introductionmentioning
confidence: 99%